The value relevance of risk-related disclosure: Does the tone of disclosure matter? - Tamer Elshandidy; Cheng Zeng (Borsa İstanbul Review, 2022)
This paper investigates whether risk-related disclosure, which includes aggregate risk disclosure and its tone, including upside and downside risk disclosures, is value relevant for investors in the UK market. Based on 1941 firm-year observations for nonfinancial firms listed on the FTSE All-Share, we employ fixed-effect estimations and find that the value relevance of aggregate risk information is not statistically observable unless a distinction is made in its tone. Specifically, upside- (downside-) risk disclosure significantly increases (decreases) stock prices. We also find that the value relevance of risk information exhibits cross-sectional variations conditional on firms' growth and profitability. In particular, we find an asymmetric response of stock prices to upside- and downside-risk disclosures for high-growth firms but not those with low growth. In addition, profit-making firms, but not loss-making firms, provide upside and downside disclosures that significantly influence stock prices. Our paper contributes to the extant research on value relevance and risk reporting by providing new evidence on the extent to which, and how, combining the accounting numbers that are examined extensively in prior research with non-accounting information (i.e., risk information) is important for observing value relevance. Our paper also advances prior research on the usefulness of risk disclosure by looking at the tone of this information and how the market responds to each type of disclosure.
Keywords: G24; G32; M41; M48; 330; Automated textual analysis; Risk-related disclosure; Upside and downside-risk disclosures; Value relevance